Bankruptcy proceedings of empty estates: a Time-Driven Activity-Based Costing-analysis for the trustee - Vandenbossche, Gauthier; De Groote, Bertel (European Insolvency and Restructuring Journal, 2025)
This paper examines the adequacy of the Belgian state funding model for remunerating trustees in empty estate bankruptcy cases, where a fixed fee is provided to the trustee regardless of the case’s complexity and his workload. Using a Time-Driven Activity-Based Costing (TDABC) model, the study calculates the actual cost of trustees’ activities, comparing this with the fixed fee trustees receive for administering empty estate cases. The findings indicate that in 90% of the cases, the fixed fee does not cover the trustees’ costs, revealing significant ‘virtual salary deficits’. The analysis highlights the most resource-intensive activities and time drivers. Potential cost-saving measures, such as eliminating claim verification, are suggested. The study also advocates for a more flexible fee structure that reflects case complexity and provides adequate incentives for trustees linked to the broader societal role of bankruptcy proceedings. This research offers new insights into the policy debate on trustee remuneration and the empty estate problem.